Evaluating Sorghum bicolor resistance to Solidago canadensis invasion under different nitrogen scenarios - Anas, Muhammad; Khan, Irfan Ullah; Alomrani, Sarah Owdah; Nawaz, Mohsin; Huang, Zhi-Yun; Alshehri, Mohammed Ali; Al-Ghanim, Khalid A.; Qi, Shan-Shan; Li, Jian; Dai, Zhi-Cong; Ali, Shafaqat; Du, Dao-Lin (Frontiers in Plant Science, 2024)
Ecosystem exposure to a biological invasion such as plant invasion could contribute to the extinction of native species and loss of productivity and ecosystem balance. Solidago canadensis (S. canadensis) is a highly invasive species that has formed monocultures in China, Europe, Asia, Australia, and New Zealand. It was designated as a notorious invasive species by the Chinese government. It has adversely affected the agroecosystem’s ability to germinate various plant seeds, including wheat, lettuce, and pepper, which could lead to food insecurity. This study was conducted to control the invasive species S. canadensis by utilizing a competitive species, Sorghum bicolor (S. bicolor) as a cover plant. Sorghum bicolor exudes allelochemicals such as sorgoleone from its roots which suppress the photosystem II activity of nearby plants. The synthesis of sorgoleone depends on a supply of nitrogen. The present study involved the cultivation of S. bicolor alongside the invasive species S. canadensis, with three different invasion levels (high, medium, and low) and three different nitrogen forms (ammonical, nitrate, and combined ammonical and nitrate nitrogen) applied as a modified Hogland solution. S. bicolor expressed higher performance over the invasive species under ammonical and combined nitrogen forms under low and medium invasion levels. Furthermore, even at greater levels of invasion, S. bicolor was not suppressed by S. canadensis. However, the plant height and dry biomass of S. bicolor were significantly high across both nitrogen forms. Leaf area, CO2 uptake, and photosystem II activity of S. canadensis were unable to sustain its growth under the low invasion condition. The plant biomass of S. canadensis was suppressed by up to 80% and the relative dominance index of S. bicolor was 5.22 over S. canadensis. There was a strong correlation between CO2 uptake, leaf area, and plant biomass. Principal component analysis showed that the first four components had a total variance of 96.89%, with principal component 1 (PC1) having the highest eigenvalue at 18.65. These promising findings suggested that S. bicolor, whose high intensity might be employed to control the invasion process for environmental safety, might be able to recover the barren ground that S. canadensis had invaded.